Circularly Polarized Fluorescent Helicene‐Boranils: Synthesis, Photophysical and Chiroptical Properties. Issue 29 (22nd April 2021) - Macé, Aurélie; Hamrouni, Khaoula; Gauthier, Etienne S.; Jean, Marion; Vanthuyne, Nicolas; Frédéric, Lucas; Pieters, Grégory; Caytan, Elsa; Roisnel, Thierry; Aloui, Faouzi; Srebro‐Hooper, Monika; Carboni, Bertrand; et al.
Abstract: Mono‐ and di‐boranil‐substituted helicenes were prepared by BF2 ‐borylation of the corresponding anils, readily synthesized by condensation of 2‐amino‐ and 2, 15‐diamino‐helicenes with 4‐(diethylamino)salicylaldehyde. After enantiomeric resolution using HPLC, their chiroptical properties including circularly polarized fluorescence in solution and in PMMA films were investigated and rationalized with the help of NMR, X‐ray and quantum‐chemical calculations. Abstract : Helicene‐mono‐ and bis‐boranils have been prepared in enantiopure forms. The chiroptical (electronic circular dichroism and optical rotation) and photophysical properties (unpolarized and circularly polarized luminescence) of these new chiral emissive helicenes have been studied both experimentally and theoretically and highlight their combined helical and axial chirality effects.